Pregnancy experience associated to fetal abnormality incompatible with life - Arancibia Heger, Mariana; Silva Dreyer, Anamaría; Pantoja Molina, Francisco (Acta Bioethica, 2018)
Increasing precocity of fetal diagnosis allows parents an early knowledge of the health conditions of their unborn child. When a fetal abnormality incompatible with life is diagnosed, the pregnant woman receives an emotional shock and faces ethical dilemmas, and the health care system must deal with complexities in quality service provision. In a qualitative study at the Aconcagua Valley, seven male and female midwives, a psychologist and three women that gave birth to newborns that died due to their condition, were interviewed. The interviews shed light on the women´s processes at their pregnancy, childbirth and postnatal stages, and on their impression of the healthcare system´s response: the diagnosis has a high emotional impact and the pregnancy evolves with an important psychological cost for the pregnant woman, who faces the situation with ambivalent feelings, and as a prolonged period of mourning. For the health professionals, particularly for midwives assisting these cases, the situation is complex, and even though the professionals strive for improved care, the process should be facilitated by developing key aspects tending towards an integral approach to health provision, even in the context of a probable legalized therapeutic abortion.